The impact of digital transformation on supply chain performance in oil and gas industry - Nur Syakilla, Mohd Baharim (2024)
This study investigates the impact of digital transformation on supply chain performance in the oil and gas industry. With the rapid advancement of technologies such as Artificial Intelligence (AI), Internet of Things (IoT), Blockchain Technology (BT), and Cloud Computing (CC), understanding their effects on supply chain efficiency, responsiveness, and transparency has become increasingly critical. Employing a quantitative research design, the study utilized a cross-sectional survey distributed to 150 professionals within the oil and gas sector. The survey, consisting of validated measurement scales, gathered data on perceptions of digital transformation technologies and their influence on supply chain performance. Statistical analysis, including correlation and regression techniques, was conducted using SPSS to explore the relationships between the technologies and performance outcomes. The results reveal that all four digital transformation technologies—AI, IoT, BT, and CC—positively impact supply chain performance. The findings underscore the importance of integrating these technologies into supply chain strategies to achieve enhanced efficiency, transparency, and responsiveness. Organizations in the oil and gas industry are encouraged to invest in and adopt these digital solutions to maintain a competitive edge and optimize their supply chain operations. This study contributes to the existing body of knowledge by providing empirical evidence on the specific impacts of digital transformation technologies on supply chain performance within the oil and gas industry. It offers actionable insights for industry practitioners and policymakers aiming to leverage digital advancements for improved supply chain management